2010
DOI: 10.1111/j.1365-2966.2010.17684.x
|View full text |Cite
|
Sign up to set email alerts
|

Nearby early-type galaxies with ionized gas: the UV emission from GALEX observations★

Abstract: We present GALEX far-ultraviolet (FUV, λ eff = 1538 Å) and near-ultraviolet (NUV, λ eff = 2316 Å) surface photometry of 40 early-type galaxies (ETGs) selected from a wider sample of 65 nearby ETGs showing emission lines in their optical spectra. We derive FUV and NUV surface brightness profiles, (FUV−NUV) colour profiles and D 25 integrated magnitudes. We extend the photometric study to the optical r band from SDSS imaging for 14 of these ETGs. In general, the (FUV−NUV) radial colour profiles become redder wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 65 publications
(116 reference statements)
3
53
0
Order By: Relevance
“…The source position accuracy is about 0.34 arcseconds and the angular resolution of FUV and NUV is respectively 4.2 and 4.9 arcseconds. We applied a galactic dust extinction correction, A(FUV)/E(B-V)=8.376 A(NUV)/E(B-V)=8.741, to GALEX data, assuming Milky Way dust with R v =3.1 (Cardelli et al 1989;Marino et al 2011). UV emission is a good indicator of the dust content and star formation rate of galaxies when compared with optical data.…”
Section: Uv Datamentioning
confidence: 99%
“…The source position accuracy is about 0.34 arcseconds and the angular resolution of FUV and NUV is respectively 4.2 and 4.9 arcseconds. We applied a galactic dust extinction correction, A(FUV)/E(B-V)=8.376 A(NUV)/E(B-V)=8.741, to GALEX data, assuming Milky Way dust with R v =3.1 (Cardelli et al 1989;Marino et al 2011). UV emission is a good indicator of the dust content and star formation rate of galaxies when compared with optical data.…”
Section: Uv Datamentioning
confidence: 99%
“…4, we study the relationship between stellar population parameters versus morphology on a broader luminosity baseline, by adding the bright ETGs of A07. Sersic indices were measured from SDSS images for 6 galaxies among the subset of the A07 sample (Marino et al 2010). Bulge-to-total light fractions for the A07 sample are not available.…”
Section: Correlations With Morphologymentioning
confidence: 99%
“…For the following run2 galaxies, the nebular metallicities lie clearly below the stellar metallicity values: NGC 1169, NGC 2962 (in agreement with Marino et al 2011), and NGC 4394. Only NGC 4394 is classified as a LINER.…”
Section: Comparison Of the Nebular Gas Abundances With The Distributimentioning
confidence: 69%
“…Storchi-Bergmann et al (1994) concluded that both abundance measurements are well-correlated for star-forming galaxies. However, recent work (Marino et al 2011) suggests, as derived from HI and GALEX UV imaging, the presence of current star formation activity in early-type galaxies with emission lines. This sort of galaxy rejuvenation could be due to external gas re-fueling.…”
Section: Comparison Of the Nebular Gas Abundances With The Distributimentioning
confidence: 99%